Disseminated BCG in primary immunodeficiency (Indian Journal of Case Reports, 2024)
Bacillus Calmette–Guerin (BCG) vaccination is administered at birth in all tuberculosis (TB)-endemic countries as part of the immunization schedule. Usually, only local complications are seen with this vaccine; however, disseminated mycobacterial infection is possible in the immunocompromised. Our case is a 6-month-old girl who presented with pneumonia, loose stools, oral candidiasis, and failure to thrive. Blood counts showed leukopenia and chest X-ray showed the absence of thymus. Flow cytometry and immunoglobulin profile were suggestive of primary immunodeficiency (PID), possibly severe combined immunodeficiency (SCID), and hence, the child was started on cotrimoxazole and monthly immunoglobulin prophylaxis. A month later, the child presented with apathy, loss of acquired development milestones, indurated BCG site with local lymph node enlargement, multiple subcutaneous nodules, and hyperintensities in the ulna in the magnetic resonance imaging bone screen. Acid–fast bacilli were isolated from both BCG sites and subcutaneous nodules on the trunk. Disseminated BCG should be suspected in any case of PID if they have received the BCG vaccine at birth. This case also highlights the need for neonatal screening for SCID.